The PII protein interacts with the Amt ammonium transport and modulates nitrate/nitrite assimilation in mycobacteria - Ensinck, Delfina; Gerhardt, Edileusa C. M.; Rollan, Lara; Huergo, Luciano F.; Gramajo, Hugo; Diacovich, Lautaro (Frontiers in Microbiology, 2024)
PII proteins are signal transduction proteins that belong to a widely distributed family of proteins involved in the modulation of different metabolisms in bacteria. These proteins are homotrimers carrying a flexible loop, named T-loop, which changes its conformation due to the recognition of diverse key metabolites, ADP, ATP, and 2-oxoglutarate. PII proteins interact with different partners to primarily regulate a set of nitrogen pathways., and Iin some organisms, PII proteins can also control carbon metabolism by interacting with the biotin carboxyl carrier protein (BCCP), a key component of the acetyl-CoA carboxylase (ACC) enzyme complex, inhibiting its activity with the consequent reduction of fatty acid biosynthesis. Most bacteria contain at least two PII proteins, named GlnB and GlnK, with different regulatory roles. In mycobacteria, only one PII protein was identified, and the tridimensionalthree-dimensional structure was solved, however, its physiological role is unknown. In this study we purified the Mycobacterium tuberculosis (MtubM. tb) PII protein, named as GlnB, and showed that it weakly interacts with the AccA3 protein, the α subunit shared by the three different, and essential, Acyl-CoA carboxylase complexes (ACCase 4, 5 and 6) present in MtubM. tb. A M. smegmatis deletion mutant, ∆MsPII, exhibited a growth deficiency on nitrate and nitrite as unique nitrogen sources, and accumulated nitrite in the culture supernatant. In addition, MtubM. tb PII protein was able to interact with the C-terminal domain of the ammonium transporter Amt establishing the ancestral role for this PII protein as a GlnK functioning protein.